World Sustainable Energy Days Next 2014 Conference Proceedings - Dell, Gerhard; Egger, Christiane; SpringerLink (Online service) (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Vieweg, 2015)
These conference proceedings contain contributions to one of Europe’s largest annual conferences on energy efficiency and renewable energy. From two main fields – biomass and energy efficiency in buildings – contributions offer an insight into the research work and the scientific findings and developments of young researchers from all over the world. The papers were selected by a high-level scientific committee for oral presentation. They also communicate results, trends and opinions that will concern and influence the world’s energy experts and policy makers over the next decades. The conference was held from 26-27 February 2014. The conference The conference is organized by the Energy Agency of Upper Austria (OÖ Energiesparverband) and held in Wels annually in February or March. It attracts more than 700 experts from over 50 countries every year. The Editors Christiane Egger is the deputy managing director of the OÖ Energiesparverband and the Manager of the Ökoenergie-Cluster, a network of 160 companies active in sustainable energy. Dr. Gerhard Dell is the managing director of the OÖ Energiesparverband and the Energy Commissioner of Upper Austria.
Keywords: Energy systems; Renewable energy resources; Energy policy; Energy and state; Energy harvesting; Energy efficiency; Energy Systems; Renewable and Green Energy; Energy Policy, Economics and Management; Energy Harvesting; Energy Efficiency; Renewable and Green Energy